Sustainability Assesment Of Organic And Conventional Rice Farming In The Bondowoso Agricultural Landscape, East Java, Indonesia (Jurnal Agribisnis Indonesia, 2026)
The dependency level of Indonesian rice farmers on chemical fertilizers and chemical pesticides for pest and disease control is considerably high, accounting for over 75% of the total chemical inputs used. Excessive use of these chemical substances has led to various environmental crises and ecosystem degradation, ultimately reducing rice productivity. One strategy to mitigate this dependency is through the adoption of organic rice farming practices. Therefore, it is essential to conduct an in-depth analysis to evaluate and compare the performance of organic and conventional rice farming systems, particularly in terms of sustainability. This study aims to compare the sustainability of organic and conventional rice farming systems in Bondowoso Regency, East Java Province. A total of 158 respondents were selected using a Proportionate Non Probabilistic Sampling method, comprising 64 organic and 94 conventional rice farmers. The sustainability of these farming systems, the study employed a Multidimensional Scaling (MDS) approach, focusing on five key dimensions: economic, social, environmental, institutional, and technological aspects. The results of the analysis revealed that the sustainability index for organic rice farming was 84.623, categorized as good sustainable. In contrast, the sustainability index for conventional rice farming was 46.401, indicating a less sustainability. These findings suggest that organic rice farming systems exhibit a higher degree of sustainability compared to conventional systems in the study area. The findings of this study provide important implications of agricultural development policies, particularly in promoting environmentally friendly and sustainable rice farming practices that can enchance farmer welfare while reducing environmental degradation.